2021
DOI: 10.1371/journal.pone.0244581
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of drug susceptible Tuberculosis in private health facilities in Lagos, South-West Nigeria

Abstract: Background The Lagos State Tuberculosis, Buruli Ulcer, and Leprosy Control Program (LSTBLCP) started engaging private hospitals under the Public-Private Mix (PPM) Program in 2008. The study aimed to evaluate the trend and predictors of successful Tuberculosis (TB) treatment outcomes of patients managed across these private health facilities between 2010–2016 in Lagos, Nigeria. Methods Retrospective review of TB treatment register and treatment cards of patients commenced on TB treatment between January 2010 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 34 publications
1
40
2
1
Order By: Relevance
“…This systematic review used the procedures specified in the PRISMA guidelines as a guide for reporting systematic reviews and meta-analyses (Page et al, 2021). Inclusion criteria are studies that reported the determinants and outcomes of TB treatment, have access to a full text, are in English, and are published in the last ten years, considering that the increase in TB has occurred in several countries in Asia and Africa since 2013 (WHO, 2020), which is in line with the results of the study that an increase in TB diagnoses in Nigeria has occurred since 2010, and an increase in TB incidence in Ethiopia has occurred since 2012 (Muluye et al, 2018;Oladimeji et al, 2021). Articles will be excluded if the study location is not in the Asian and African continents, the study design is a systematic review, or the study population is MDR TB patients or TB with comorbidities.…”
Section: Methodssupporting
confidence: 67%
See 1 more Smart Citation
“…This systematic review used the procedures specified in the PRISMA guidelines as a guide for reporting systematic reviews and meta-analyses (Page et al, 2021). Inclusion criteria are studies that reported the determinants and outcomes of TB treatment, have access to a full text, are in English, and are published in the last ten years, considering that the increase in TB has occurred in several countries in Asia and Africa since 2013 (WHO, 2020), which is in line with the results of the study that an increase in TB diagnoses in Nigeria has occurred since 2010, and an increase in TB incidence in Ethiopia has occurred since 2012 (Muluye et al, 2018;Oladimeji et al, 2021). Articles will be excluded if the study location is not in the Asian and African continents, the study design is a systematic review, or the study population is MDR TB patients or TB with comorbidities.…”
Section: Methodssupporting
confidence: 67%
“…Internal factors consist of 11 determinants from within the TB patient, namely age, gender, education, HIV status, TB location, treatment category, alcohol consumption, drug use, smoking, type of ARB (Acid Resistant Bacteria), and comorbidities (Ahmad et al, 2020;Atif et al, 2014;Babalik et al, 2014;Banerjee et al, 2020;DesJardin et al, 2020;García-Basteiro et al, 2016;Habte et al, 2020;Khazaei et al, 2016;Mohammadzadeh et al, 2016;Mulogo et al, 2017;Muluye et al, 2018;Mundra et al, 2019;Ogbudebe et al, 2018;Oladimeji et al, 2021;Sadana et al, 2020;Sahyog et al, 2018;Son et al, 2021;Tesema et al, 2020;Tetteh et al, 2018;Umeokonkwo et al, 2020;Wen et al, 2018). 13 articles described age as an internal factor for TB treatment outcomes (Ahmad et al, 2020;Atif et al, 2014;Babalik et al, 2014;Habte et al, 2020;Mundra et al, 2019;Ogbudebe et al, 2018;Oladimeji et al, 2021;Sadana et al, 2020;Son et al, 2021;Tesema et al, 2020;Tetteh et al, 2018;Umeokonkwo et al, 2020;Wen et al, 2018). The likelihood of a successful treatment outcome was higher among patients aged 15-24 years, compared to patients younger than 14 years (Tesema et al, 2020), and over 61 years (Ahmad et al, 2020;Habte et al, 2020).…”
Section: Internal Factorsmentioning
confidence: 99%
“…Outside of Nigeria, most studies examining private sector TB service delivery in LMICs including Ethiopia, India, Kenya, the Philippines, and Thailand, have identified important shortcomings in effectiveness of tuberculosis cases management by private clinicians and pharmacists [9][10][11][12][13][14][15][16][17]. Within Nigeria, several studies have examined treatment success rates (TSR) in clinical facilities participating in small-scale PPM pilots in Anambra, Imo, Kaduna, Lagos, Ogun, and Plateau states [7,[18][19][20][21][22][23]. Although these studies found that observed TSR for private sector patients was lower than Nigeria's national treatment success target of 90 percent, these rates were often comparable to TSR reported for public sector patients in those states [7,[18][19][20][21][22][23], which supports continued scale up of PPM in Nigeria to increase access to care.…”
Section: Introductionmentioning
confidence: 99%
“…Within Nigeria, several studies have examined treatment success rates (TSR) in clinical facilities participating in small-scale PPM pilots in Anambra, Imo, Kaduna, Lagos, Ogun, and Plateau states [7,[18][19][20][21][22][23]. Although these studies found that observed TSR for private sector patients was lower than Nigeria's national treatment success target of 90 percent, these rates were often comparable to TSR reported for public sector patients in those states [7,[18][19][20][21][22][23], which supports continued scale up of PPM in Nigeria to increase access to care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation